2019
DOI: 10.1158/0008-5472.can-18-2207
|View full text |Cite
|
Sign up to set email alerts
|

IFNγ-Induced IFIT5 Promotes Epithelial-to-Mesenchymal Transition in Prostate Cancer via miRNA Processing

Abstract: IFNg, a potent cytokine known to modulate tumor immunity and tumoricidal effects, is highly elevated in patients with prostate cancer after radiation. In this study, we demonstrate that IFNg can induce epithelial-to-mesenchymal transition (EMT) in prostate cancer cells via the JAK-STAT signaling pathway, leading to the transcription of IFN-stimulated genes (ISG) such as IFN-induced tetratricopeptide repeat 5 (IFIT5). We unveil a new function of IFIT5 complex in degrading precursor miRNAs (pre-miRNA) that inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(100 citation statements)
references
References 37 publications
8
87
0
2
Order By: Relevance
“…Although IFITs are involved in the host immune response and antiviral defense, emerging research studies have shown their involvement in malignant progression (Lai et al, 2008(Lai et al, , 2013Niess et al, 2015;Zhang et al, 2016;Ohsugi et al, 2017;Yang et al, 2017;Zhao et al, 2017;Chen et al, 2018;Lo et al, 2018Lo et al, , 2019Nushtaeva et al, 2018;Shen et al, 2018;Huang et al, 2019). The epithelial-mesenchymal transition (EMT) is a biological mechanism in which epithelial cells convert into a mesenchymal phenotype to acquire increased cell invasion and migration capacity as well as resistance to apoptosis (Kalluri and Weinberg, 2009), which lead to metastasis (Yilmaz and Christofori, 2009).…”
Section: Ifits In Malignant Progressionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although IFITs are involved in the host immune response and antiviral defense, emerging research studies have shown their involvement in malignant progression (Lai et al, 2008(Lai et al, , 2013Niess et al, 2015;Zhang et al, 2016;Ohsugi et al, 2017;Yang et al, 2017;Zhao et al, 2017;Chen et al, 2018;Lo et al, 2018Lo et al, , 2019Nushtaeva et al, 2018;Shen et al, 2018;Huang et al, 2019). The epithelial-mesenchymal transition (EMT) is a biological mechanism in which epithelial cells convert into a mesenchymal phenotype to acquire increased cell invasion and migration capacity as well as resistance to apoptosis (Kalluri and Weinberg, 2009), which lead to metastasis (Yilmaz and Christofori, 2009).…”
Section: Ifits In Malignant Progressionmentioning
confidence: 99%
“…IFIT5 expression was also inversely correlated with miR-363 expression in prostate cancer. IFIT5 is involved in the degradation of miR-363 and can form a complex with miR-101 and miR-128 to promote prostate cancer progression by inducing EMT (Lo et al, 2018).…”
Section: Ifits In Malignant Progressionmentioning
confidence: 99%
See 2 more Smart Citations
“…IFN-c can induce epithelial-tomesenchymal transition (EMT) in PCa cells via the JAK-STAT signaling pathway [75], and STAT3 may directly mediate EMT progression and regulate ZEB1 expression in CRC [76] PCa progression, cell proliferation, and inhibition of apoptosis [51,52] No direct analysis of these pathways in CTCs Wnt/ β-catenin Dysregulation of Wnt/β-catenin signaling has been implicated in the development of cancer in different tissues such as lung, skin, liver, and prostate [52], via regulating Zeb1 in CRC [77] Wnt/β-catenin pathway promotes the metastatic spread of prostate cancer cells by inducing EMT [78] Epithelial type CTCs and activation of Wnt/β-catenin signaling in lung cancer cells [79]. No report in PCa CTCs Notch Crosstalk between the Jagged1/Notch and JAK/STAT3 signaling pathways by promoting EMT through Jagged-1 in ovarian cancer [80] Notch signaling results in prostate tumor recurrence via EMT [81] Increased production of ROS results in the upregulation of Notch1 in CTCs in metastatic breast and melanoma cancer [82].…”
Section: Jak/ Statmentioning
confidence: 99%